Medicaid Expansion in Maine Significantly Reduced Uncompensated Care Costs during the COVID-19 Pandemic - Rhodes, Jordan (Maine Policy Review, 2024)
This study examines the impact of Maine’s 2019 Medicaid expansion through the Affordable Care Act on hospitals’ uncompensated care costs. The author finds that this expansion reduced uncompensated care costs by an average of 26 percent per year, leading to a $126 million reduction in uncompensated care costs during the first two years of the COVID-19 pandemic. The most pronounced reduction in costs occurred across larger, general acute care hospitals. When comparing bad debt vs charity care, the reduction in uncompensated care costs is driven by a steep decline in reported charity care costs. This decline offsets increases in bad debt expenses in 2020 across smaller, critical access hospitals. The results highlight Medicaid expansion’s effectiveness in lowering uncompensated care costs during the first two years of the COVID-19 pandemic in Maine.
Keywords: Medicaid Expansion; Hospital Finances; Uncompensated Care Costs; Health Economics